Demographic and clinical characteristics of patients with type 1 diabetes mellitus initiating sodium-glucose cotransporter 2 inhibitors in Japan: A real-world administrative database analysis. (August 2022) - Abiru, Norio; Shoji, Shingo; Kosakai, Yoshinori; Snijder, Robert; Asakawa, Keiko; Rokuda, Mitsuhiro
Highlights: Patients who had SGLT2i (with insulin) had higher HbA1c than those who had insulin. Patients who had SGLT2i (with insulin) had higher BMI than those who had insulin. Total daily doses of insulin decreased after the first SGLT2i prescription. HbA1c, BMI, HDL, and SBP improved after the first SGLT2i prescription. Abstract: Aims: To investigate the baseline demographic and clinical characteristics of patients with type 1 diabetes mellitus (T1DM) newly treated with a sodium-glucose cotransporter 2 inhibitor (SGLT2i) as an add-on to insulin, or treated with insulin alone or in combination with oral anti-diabetic drugs other than an SGLT2i. Methods: Retrospective study using data from the JMDC database (December 21, 2018, to October 31, 2020). Included patients with T1DM treated with an SGLT2i (add-on to insulin) (n = 1027) or with insulin (n = 4320). Baseline demographic and clinical characteristics were summarized, and change in insulin dose and efficacy outcomes, including hemoglobin A1c (HbA1c) and body mass index (BMI), before and after the first SGLT2i or insulin prescription were evaluated. Results: The SGLT2i add-on group had higher HbA1c and BMI than the insulin group. Daily insulin doses decreased from immediately before to after the first SGLT2i prescription. HbA1c and BMI improved from baseline to after the first SGLT2i prescription. Conclusions: This large real-world study reported the baseline demographic and clinical characteristics of patients with T1DM newly treated with an SGLT2i in Japan. The findings may guide the appropriate use of SGLT2i and support large-scale database studies in T1DM research.